Theoretical and Linearity Analysis for Pressure Sensors and Communication System Development. (11th September 2014) - Jeong, Taikyeong
For the safety, reliability, and fuel economy, new road vehicles and automotive pressure sensor are being equipped with tire pressure measurement system (TPMS) in the vehicle. This paper describes the theoretical analysis and linear behavior of direct-type tire pressure sensor while the vehicle is operating. A rugged pressure sensor, thin-film piezoresistive pressure sensor, design is presented as a modular design approach for TPMS, where all the main parts of the TPMS can be connected together for easiness in integration, maintenance, and replaceability. This can also result in reducing replacement cost as well as maintaining linearity behavior of pressure sensor's property. Three-dimensional model was analyzed with material properties; the resonance frequency of the model calculated is 24 kHz and sensitivity is calculated to be 1.2 µ V/V·kPa. Our result shows that a thin-film technology of sensor design is still a viable solution for vehicular sensor and system measurement development.